Work of a Nation: Christian Funerary Ecumenism and Institutional Disruption in Swaziland. Issue 2 (4th March 2018) - Golomski, Casey
Abstract : This article traces how contemporary funerary practices – foodways, prayer and burial co-operative participation – configure a Christianised public culture in Swaziland that draws from ordinary citizens' religious, ritual and political work and membership in diverse Christian churches. This kind of grassroots ecumenism importantly challenges the potency of orthodox institutional ecumenical projects of religious elites in the kingdom. These projects include attempts to legislate Christianity as an official religion and the building of a national interdenominational church, both of which have failed to materialise. Exploring this emergent tension between religious institutions' ideological goals versus communities' practical engagement on pressing social problems invites a rethinking of how citizens produce public cultures. Research is based on intermittent fieldwork at funerals, burial co-operatives, family ceremonies and churches, interviews with local church leaders and theologians, and document research in Swaziland between 2008 and 2015.